Diagnostic and therapeutic guidelines for pancreatic cystic tumors: recommendations of Polish Pancreatic Club experts - Durko, Łukasz; Lipiński, Michał; Adrych, Krystian; Daniluk, Jarosław; Dąbrowski, Andrzej; Durczyński, Adam; Gąsiorowska, Anita; Głuszek, Stanisław; Hartleb, Marek; Hogendorf, Piotr; Jagielski, Mateusz; Jaszczuk, Kamil; et al. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
The diagnosis, treatment, and follow-up of pancreatic cystic tumors require a careful expert consensus approach due to their diverse nature and variable potential for malignancy. In view of these challenges, a panel of experts from the Polish Pancreatic Club has developed comprehensive recommendations. These guidelines are based on the most recent literature data and reflect current advances in diagnostic imaging and therapeutic interventions. The panel conducted an extensive review of available publications, meticulously formulating each recommendation and subsequently voting on them using the GRADE system (providing the quality of evidence and recommendation strength for each statement). The guidelines emphasize the importance of advanced imaging modalities (such as computed tomography, magnetic resonance, and endoscopic ultrasound), fine needle aspiration biopsy in selected situations and applicable laboratory tests to improve diagnostic accuracy. Furthermore, treatment strategies are carefully tailored to match individual risk profiles and specific lesion characteristics. Management options range from conservative treatment with routine follow-up examinations to surgical interventions when clinical indications require such an approach. Overall, these expert recommendations provide clinicians with a valuable and reliable framework, firmly anchored in current scientific data and consensus among specialists, for effectively managing pancreatic cystic tumors in clinical practice. Ultimately, these guidelines will lead to improved patient outcomes.